THE INHIBITORY EFFECT OF TELLURIC ACID AGAINST GROWTH OF SOME BACTERIA(IN VITRO) - Eman T. Ali; Shaker.A.N.Al Jadaan (Basrah Journal of Veterinary Research)
It was found that 0.3M of telluric acid dissolved in distilled water added in to Muller-Hinton agar media inhibited the growth of some gram positive bacteria (Staphylococcus aureus, Staphylococcus albus and Streptococcus pyogenes) as well as some gram negative bacteria (Escherichia coli, Klebsiella aerogenes and Pseudomonas aeruginosa). Higher concentration of telluric acid solution in to the media inhibited growth of bacteria more strongly